CARTOGRAPHIE PAR SIG DE L’ALÉA D’ÉBOULEMENT DANS LE BASSIN VERSANT DE DADES (HAUT ATLAS CENTRAL), MAROC - El Aaggad, Nadia; Algouti, Ahmed; Algouti, Abdellah; Amaya, Adama (European Scientific Journal, ESJ, 2015)
Landslides constitute the natural events which threaten the goods and the persons. They include the whole natural or man-made movements more or less rough of soil or subsoil. The Dades watershed parameters, strong topographic slopes, lithology, geological structure and vegetation cover, make it an unstable and sensitive area of landslides. The magnitude of this phenomenon was most remarkable in the upstream part and plays a key role of basin evolution. In this work the landslide term include the rock slides of rock masses of various sizes which, mainly manifest in the carbonate and conglomerates formations respectively of Jurassic and Mio-Pliocene age, and seriously threaten the homes and the road network. In this work realizing of hazards map of Dades basin was based on field investigation, satellites data, and processing of digital elevation model using GIS softwares. This mapping allows an overall appreciation of basin susceptibility at ground instability. This work is a first backgrounder and sensibilization of the landslides risk in study area.